Uji Aktivitas Antioksidan Ekstrak N-Heksana, Etil Asetat, Dan Etanol Bonggol Pisang Kepok (Musa paradisiaca L.) Dengan Metode DPPH (1,1-diphenyl-2-picrylhydrazyl) - Supriatnini, Ai; Farhan, Zahara; Hasyim, Dadang Muhammad (Jurnal Medika Farmaka, 2024)
Free radicals are atoms, groups of atoms, or molecules that have one or more unpaired electrons in the outermost orbital and are highly reactive. Free radicals are more able to attack cells in the body, especially those that are vulnerable, causing various diseases such as premature aging, cancer, liver, and other degenerative diseases. Antioxidants are compounds that can be considered as free radical reactivity. Sources of natural antioxidants are plants which generally contain phenolic compounds. Phenolic or polyphenolic compounds can be in the form of flavonoids. The ability of flavonoids as antioxidants has been widely studied, where flavonoids have the ability to reduce free radicals and also act as anti-free radicals. Kepok banana hump contains flavonoid compounds. The aim of this study was to determine the antioxidant activity of n-hexane, ethyl acetate, and ethanol extracts of kepok banana weeds using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method based on the IC50 value. The principle of this method is the decrease in color intensity or absorbance of the DPPH solution which is proportional to the increase in the concentration of antioxidant compounds. This research was carried out experimentally, collection and processing of plants, experience of plant materials, manufacture of extracts, and testing of antioxidant activity. The kepok banana weevil was extracted by maceration method using various solvents based on the level of polarity, namely n-hexane, ethyl acetate, and ethanol in stages. The extraction results obtained thick extracts of n-hexane, ethyl acetate and ethanol as much as 2.12 g (0.70%), 1.09 g (0.36%), and 4.64 g (1.54%) . The third antioxidant activity test of kepok banana weevil extract using the DPPH method using a UV-Vis spectrophotometer at a wavelength of 519.0 nm with a series of concentrations of 100 g/mL, 150 g/mL, 200 g/mL, 250 g/mL, and 300 g/mL. The results of the antioxidant activity test using the DPPH method showed that the n-hexane, ethyl acetate, and ethanol extracts of kepok banana weeds had IC50 values of 197.5 g/mL and 257.30 g/mL, 142.51 g/mL, respectively. The ethanol extract had moderate antioxidant activity compared to the n-hexane and ethyl acetate extracts.